An Investigation Into the Effect of Verjuice Concentration on the Physicochemical and Textural Properties of Beef - Fereshteh Sabzi (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2017)
This study was performed in order to examine the effect of verjuice concentration on the physicochemical and textural properties of beef Biceps femoris, which aimed at improving its tenderness and enhancing its marketability. To that end, verjuice (0, 30, 70 and 100%) and sodium chloride (2% w/w) were injected into the beef pieces with dimensions of 3×15×15 cm3 (10% of each piece initial weight). Then, for the uniform distribution of the solution on the surface and deep parts of the beef, the samples were immersed in verjuice solution (with the same concentration as was injected and at a ratio of 4:1) and stored at 4 °C for 12 h. The results showed that as verjuice concentration increased, pH decreased significantly (P<0.05). Furthermore, storage in verjuice solution caused a significant increase (P<0.05) in the weight gain, cooking loss and water holding capacity (WHC) of the samples. The color parameters of L* and b* of the treated samples were significantly (P<0.05) higher than those of the control, whereas their a* were lower. The samples stored in verjuice 100% for 12 h had the highest Myofibrillar Fragmentation Index (MFI) and sarcomere length, while they had the lowest Warner-Bratzler Shear Force (WBSF). Therefore, it was concluded that verjuice solution can act as a replacement for the chemical tenderizers applied in the meat industry without any negative effect on other quality attributes.